Transformation of Conventional Transactions to Sharia At Sulit Air Sepakat Cooperative of Padang City - Aimon, Hasdi; Putra, Hari Setia; Honesty, Helga Nuri; Wahyuni, Ika Sari (Suluah Bendang: Jurnal Ilmiah Pengabdian Kepada Masyarakat, 2020)
This study aims to look at the preferences of members Sulit Air Sepakat (SAS) Cooperative of Padang City to transform conventional transactions into sharia. The SAS Cooperative is one of the cooperatives in Padang City, whose members come from members of the Padang City SAS Association. The SAS Cooperative has experienced ups and downs in its development, so the identification of problems from the causes include non-performing loans of members, not yet fulfilled the wishes or needs of members as expected, decreasing member loan transactions and decreasing cooperative Business Results. Data obtained based on observations to all members of the Padang City SAS Cooperative with 80 respondents using multiple linear analysis methods. The results of this study indicate that all independent variables namely halal and Toyyiban, services or burdens offered are not too little or excessive, the benefits obtained, be careful in using wealth, social behavior and the identity of Islamic cooperatives are significant towards the dependent variable namely the willingness of cooperative members to transform conventional transactions into sharia. The recommendation of this study is that the cooperative management must immediately transform conventional transactions to sharia in accordance with the wishes of cooperative members and provide training to members about the concept and system of sharia transactions.